An ACA 1 mm survey of HzRGs the ELAIS-S1: survey description and first results. Issue 4 (22nd May 2021) - Messias, Hugo G; Hatziminaoglou, Evanthia; Hibon, Pascale; Mroczkowski, Tony; Matute, Israel; Lacy, Mark; Mason, Brian; Martín, Sergio; Afonso, José M; Fomalont, Edward; Amarantidis, Stergios; Antón, Sonia; et al.
ABSTRACT: Radio-emitting jets might be one of the main ingredients shaping the evolution of massive galaxies in the Universe since early cosmic times. However, identifying early radio active galactic nuclei (AGNs) and confirming this scenario have been hard to accomplish, with studies of samples of radio AGN hosts at z > 2 becoming routinely possible only recently. With the above in mind, we have carried out a survey with the Atacama Compact Array (ACA or Morita Array) at 1.3 mm (rms = 0.15 mJy) of 36 high-redshift radio AGN candidates found within 3.9 deg 2 in the ELAIS-S1 field. The work presented here describes the survey and showcases a preliminary set of results. The selection of the sample was based on three criteria making use of infrared (IR) and radio fluxes only. The criterion providing the highest selection rate of high-redshift sources (86 per cent at z > 0.8) is one combining an IR colour cut and radio flux cut ( S 5.8μm / S 3.6μm > 1.3 and $S_{\rm 1.4\, GHz}\gt 1\, $  mJy). Among the sample of 36 sources, 16 show a millimetre (mm) detection. In eight of these cases, the emission has a non-thermal origin. A z sp = 1.58 object, with a mm detection of non-thermal origin, shows a clear spatial offset between the jet-dominated mm continuum emission and that of the host's molecular gas, as traced by serendipitously detected CO(5-4) emission. Among the objects with serendipitous line detections there is a source with a narrow jet-like region, as revealed by CS(6-5) emission stretching 20 kpc out of the host galaxy.